Cold War Liberation: The Soviet Union and the Collapse of the Portuguese Empire in Africa, 1961-7 - Kona, Bongani (Kronos (Bellville, South Africa), 2024)
Natalia Telepneva, Cold War Liberation: The Soviet Union and the Collapse of the Portuguese Empire in Africa, 1961-1975 (Chapel Hill: The University of North Carolina Press, 2021), 302pp., ISBN: 978-1-4696-6586-3 This absorbing account of relations between the Soviet Union and the leaders of anticolonial movements fighting to liberate Angola, Mozambique and Guinea-Bissau from Portuguese rule in the 1960s and 1970s is in part the fruit of Natalia Telepneva's doctoral dissertation under the supervision of Odd Arne Westad,1 whose own work looms large in the historiography of the Cold War. The book opens like a spy thriller with a Soviet military plane landing in Luanda on the day Agostinho Neto, leader of the Movimento Popular de Libertação de Angola (MPLA), is set to be inaugurated as the first president of independent Angola. On board the An-12 is an intelligence officer by the name of Boris Putilin, 'whose job had been to coordinate arms transfers from the Soviet Union'2 to the MPLA. Putilin is almost shot at by an Angolan solider but is rescued in time to attend the inauguration by the chief of airport security.